IDENTIFICATION OF PSEUDOMONAS AERUGINOSA STRAIN PRODUCING BIOSURFACTANT WITH ANTIFUNGAL ACTIVITY AGAINST PHYTOPHTHORA INFESTANS - Tomar, Sonica; Singh, B A; Khan, M A; Kumar, Satish; Sharma, Sanjeev; Lal, Mehi (Potato Journal, 2013)
Biosurfactant is a structurally diverse group of surface-active molecules, synthesized by microorganisms. The ability to reduce surface and interfacial tension with low toxicity and high specificity and biodegradability is a major characteristic of a biosurfactant. In the present study, soil samples were collected from agriculture fields, railway tracks and garage sites. The samples were enriched in nutrient broth, serially diluted and plated onto nutrient agar plates. A total of ninety five isolates obtained from nineteen soil samples were screened for their biosurfactant producing capacity using oil spreading, haemolytic activity, drop collapse, tilted glass slide, emulsification index (%) and emulsification assays. Out of these, the five isolates with a very good capacity to produce biosurfactant were identified as Pseudomonas aeruginosa through PCR technique using Pseudomonas genus specific primers (PA-30) and P. aeruginosa species-specific primers (PA-31, PA-33, PA-34). The crude biosurfactant extracted from one of these five isolates was identified as glycolipid class of biosurfactant which exhibited 83.33% inhibition of Phytophthora infestans growth at 100 ppm concentration when tested in-vitro using poisoned food technique.